2018
DOI: 10.1002/rnc.4289
|View full text |Cite
|
Sign up to set email alerts
|

Distributed zero‐gradient‐sum algorithm for convex optimization with time‐varying communication delays and switching networks

Abstract: Summary The distributed convex optimization problem subject to time‐varying communication delays and switching network topologies is addressed in this paper. Based on continuous‐time Zero‐Gradient‐Sum scheme, the novel distributed algorithms are proposed to minimize the global objective function which is composed of a sum of strictly convex local cost functions. In the fixed network topology case, by constructing a new Lyapunov‐Krasovskii function, two explicit sufficient conditions for the maximum admissible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…where l ii is the ith diagonal element of the Laplacian matrix L that equals ∑ N =1 a i , and hence, one has 0 < k (L) ≤ 2 for all k ≠ 1. As a consequence, 8 k (L) − 2 k (L) > 0 for all k ≠ 1, which implies that (A23) is equivalent to (23). In consideration of (A19), in what follows, it will be shown that N (L)(5 N (L) + 2) + 2 N (L)…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…where l ii is the ith diagonal element of the Laplacian matrix L that equals ∑ N =1 a i , and hence, one has 0 < k (L) ≤ 2 for all k ≠ 1. As a consequence, 8 k (L) − 2 k (L) > 0 for all k ≠ 1, which implies that (A23) is equivalent to (23). In consideration of (A19), in what follows, it will be shown that N (L)(5 N (L) + 2) + 2 N (L)…”
Section: Resultsmentioning
confidence: 91%
“…Consider the case when i , g i ∈ 1 for all i ∈ ℐ N . Under Assumption 1, if condition (23) holds, then the statements in Theorem 2 are still correct.…”
Section: Lemmamentioning
confidence: 92%
See 3 more Smart Citations